2017
DOI: 10.7717/peerj.3767
|View full text |Cite
|
Sign up to set email alerts
|

Status of gastrointestinal parasites in Red Panda of Nepal

Abstract: Red pandas are known to be highly susceptible to endoparasites, which can have a prominent impact on the population dynamics of this endangered species. There are very limited published reports on prevalence and risk of parasites in wild populations of red panda, especially localized reports. This study attempts to provide an in-depth insight of the status of endoparasites in red pandas, which is critical for strengthening conservation efforts. A total of 272 fecal samples were collected through systematic sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Any future conservation plan for red panda needs to be focused on creating species-rich, dense forests in western Nepal. This is particularly important here as most red panda habitats are situated outside of protected areas (Bista, Shrestha, Kunwar, et al, 2017;Bista, Shrestha, Sherpa, et al, 2017;Thapa et al, 2018), and silviculture practices promoting selected tree species in community forests may further jeopardize survival of this species. from 10 to 120 years (Janzen, 1976), along with limited seed dispersal ability (Mao-Ning et al, 2012;Taylor, Reid, Zisheng, & Jinchu, 1991).…”
Section: Implications For Red Panda Conservationmentioning
confidence: 99%
“…Any future conservation plan for red panda needs to be focused on creating species-rich, dense forests in western Nepal. This is particularly important here as most red panda habitats are situated outside of protected areas (Bista, Shrestha, Kunwar, et al, 2017;Bista, Shrestha, Sherpa, et al, 2017;Thapa et al, 2018), and silviculture practices promoting selected tree species in community forests may further jeopardize survival of this species. from 10 to 120 years (Janzen, 1976), along with limited seed dispersal ability (Mao-Ning et al, 2012;Taylor, Reid, Zisheng, & Jinchu, 1991).…”
Section: Implications For Red Panda Conservationmentioning
confidence: 99%
“…Through much of its spatial scale, livestock grazing has been posing serious threat either by inhabiting their suitable habitat or competing for same food resources [16]. Also, livestock has been recognized as a potential source for the transmission of zoonotic parasites [8]. Lama et al [35] found that parasites such as Trichuris spp reported from livestock is the underlying cause of bloody colitis, anaemia and sometimes even death in red pandas.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 15 linear transects of an average length of 800 m were delineated in the study area (10 in Chipchipe CF and 5 in Singhadevi CF). Every linear transect was set at an altitudinal interval of approximately 100 m following the methodology provided by [24] and practiced by [8]. The linear transects in Singhadevi CF ranged from 2310 m to 2732 m whereas transects established in Chipchipe CF covered the elevation of 2318 m to 2754 m respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several outbreaks of coccidiosis with high morbidity and about 4% CFR have been reported in chicken in Nepal (DoAH 2015(DoAH , 2016a. Interestingly, the presence of one or more species of Eimeria, Isospora, Cyclospora, Cryptosporidium, Toxoplasma, and Sarcocystis have been predominantly reported in the wild hosts like red panda, rabbit, Hodgson's Giant Flying Squirrel (Petaurista magnificus), deer, yak, and in the humans (DoAH 2015(DoAH , 2016aLama et al 2015;Bista et al 2017;Koirala et al 2016;Achhami et al 2016;Byanju et al 2011;Ghimire et al , 2007Ghimire et al , 2010Ghimire 2010Ghimire , 2018. Among these coccidia, toxoplasmosis has been predominantly reported in humans and domestic animals like sheep and goats showing the possibility of infection with meat-eating habits and cat-rearing situations in the country (Subedi et al 2018;Rai et al 1996Rai et al , 1999Sah et al 2017).…”
Section: Coccidiosismentioning
confidence: 99%